The Price of Playing Through Pain: The Link Between Physical and Behavioral Health in Former NFL Athletes. Issue 6 (November 2020) - Bush, Evelyn; Cupery, Tim; Turner, Robert W.; Sonnega, Amanda; Weir, David; Whitfield, Keith E.; Jackson, James S.
Over the past decade, media outlets have drawn attention to some of the health consequences of playing in the National Football League (NFL), including how wear-and-tear and injuries accumulated during athletes' playing years can affect their physical, emotional, and behavioral health after retirement from professional sports. Through a secondary analysis of a cross-sectional telephone survey of former NFL athletes, this study estimated logistic regression models to assess the relationship between several forms of physical pain and anger attacks, controlling for binge drinking, signs of depression, functional limitations, NFL career duration, religious service attendance, and demographic characteristics (age, marital status, race, education, income, and wealth). The analytic sample included 1030 former NFL players. Neck pain, lower back pain, headaches/migraines, and the number of sites of pain were positively and significantly related to anger attacks. There was no significant association between joint pain and anger attacks. NFL career duration was negatively associated with anger attacks, as was religious service attendance. Future research should focus on factors that protect against affective aggression in former professional athletes and how protective factors can be adapted to the broader population.